Altered toll‐like receptor responsiveness underlies a dominant heritable defect in B cell tolerance in autoimmune New Zealand Black mice. Issue 3 (19th January 2018) - Clark, Amy G.; Buckley, Elizabeth S.; Foster, Mary H.
Abstract: Systemic lupus erythematosus is a debilitating autoimmune disease in which autoantibodies and autoreactive T cells destroy kidneys and other organs. Disease is clinically and genetically heterogeneous, suggesting that underlying mechanisms vary between patients. We previously used an autoantibody transgenic mouse reporter system to examine the effect of different autoimmune backgrounds on B‐cell tolerance, failure of which is a fundamental defect in lupus. We identified a defect consistent with reversible anergy induced by endotoxin stimulation of B cells from Ig transgenic New Zealand Black (NZB) mice. Herein we report that the tolerance defect is revealed by TLR7 and TLR9 as well as TLR4 ligands, with additive effect, and is partially reversed by Mek inhibition. Gene expression analysis reveals significant differences in transcription of multiple TLR pathway genes and ptpn22 in stimulated NZB compared to B6 B cells. Additionally, the defect is detected in Ig transgenic NZB F1 hybrid strains (NZBxNZW)F1 and (B6xNZB)F1. These results implicate an inherited defect wherein NZB anergic B cells maintain coordinated TLR/BCR signaling that permits autoantibody production. Agents targeting these pathways may have therapeutic benefit in the subset of lupus patients that manifest similar defects in B‐cell regulation. Abstract : Lupus is a heterogeneous disease clinically, genetically, and mechanistically. New Zealand Black lupus mice uniquely express a dominant heritable defect in which anergic B‐cells produce autoantibodies in response to Toll‐like receptor ligands. Elucidation of underlying molecular pathways may provide novel therapeutic targets for a subset of lupus patients.